Zgromadzenia publiczne w polskim systemie prawnym i ich znaczenie dla kultury i sztuki - Gołda-Sobczak, Maria (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
Freedom of assembly is provided by Article 57 of the Constitution, as well as by numerous acts of international law. Neither the term “assembly” nor the provisions concerning the restrictions on the freedom of assembly seem to be entirely clear in the Polish legal system. Within the legal system of the Council of Europe, the European Court of Human Rights in Strasbourg has tried to define these matters. What raises particular controversy in Poland is the issue of whether assemblies can be attended by people wearing masks, who cannot therefore be identified. The attempts to change this situation have failed as a result of the position taken by the Constitutional Tribunal, but the issue seems likely to be raised again in the future.
Public assemblies in the Polish legal system and their significance for culture and arts